Candida species bloodstream infections in hospitalised children: A 10‐year experience. (4th May 2015) - Chan, Shannon; Baley, Elizabeth D; Hossain, Jobayer; Di Pentima, M Cecilia
Abstract In a 10‐year retrospective study we assessed the epidemiology of candidemia and the association between the presence and removal of indwelling central venous catheters, antifungal use and clinical outcomes among hospitalised children. Demographic and clinical information were retrieved from the electronic medical records. One hundred six episodes of candidemia were identified in 83 unique patients. Candida parapsilosis was the most prevalent (52%) species, followed by C. albicans (25%). Non‐oncologic children receiving fluconazole within 30 days of developing candidemia were most likely to develop C. parapsilosis infection (40%, P = 0.006), independent of total parenteral nutrition (odds ratio (OR) 2.5, 95% confidence interval (CI): 0.6–11, P = 0.3). Crude mortality rate was 12% and significantly higher for children less than 2 years (OR: 6.7, 95% CI: 1.9–23, P = 0.003), and those infected with C. lusitaniae (OR: 9, 95% CI: 1.6–51, P = 0.02). The aggregate use of antifungal agents decreased overtime (χ2: 16.7, P < 0.0001). Fluconazole remained the most common antifungal agent used during the study.